Analisis Pendapatan Usaha Tani Sayuran Hidroponik di CV Asma Hidroponik Kota Palu - Fitri Aisyah; Meity Ferdiana Paskual; Armin Muis; Santi Yunus; Laendatu Paembonan (AKUNTANSI 45, 2025)
The increasing demand for healthy food in urban areas has driven the development of modern agribusiness, such as hydroponics. This research aims to analyze the income and financial feasibility of hydroponic lettuce farming at CV Asma Hidroponik in Palu City as a case study. This study employed a descriptive quantitative method, with primary data collected over one month through observation and interviews. Financial feasibility was analyzed using calculations of cost, revenue, and the Revenue Cost Ratio (R/C Ratio). The results showed that a total production cost (fixed and variable) of IDR 6,380,183 generated a total revenue of IDR 7,500,000, resulting in a net profit of IDR 1,120,000 per month. An R/C Ratio of 1.18 was obtained. With an R/C Ratio greater than 1, this business is proven to be highly profitable and financially feasible to operate and develop. CV Asma Hidroponik has the potential to become a model for competitive urban agriculture. Crop diversification is recommended to expand market share and mitigate business risks.